(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The most of the production plants in Iraq apply traditional cost systems, which depend on the distribution of the total costs on the basis of which may be unconsidered, leading to the loading of the final product at unhelpful costs, whether directly or indirectly, so the system of cost-accounting based on activities (ABC) to help the unit in the evaluation and regulation of costs through the study and analysis of the activities and costs realized for those activities this study showed through the theoretical and applied study on the reality of the General Company for Textile Industries in Hilla. that the cost system applied in the company is traditional and thus load the cost is not limited by the need to develop precise cost engines by specialists with accounting and cost experience, especially with the diversity and abundance of products. The basis of one load rate is used at the level of the company as a whole, namely the productive unit, ie the total indirect industrial costs of the centers Marketing and management services) after direct exclusion whether variable or fixed as easy to track. The most important findings of the study are that the method of ABC is more accurate in measuring and determining the cost of production and the cost of a meter than the traditional method. This is reflected in the control, planning and decision making. This method provides more accurate and objective data for management. The most important recommendation of the study is to apply the cost-based system (ABC) because it leads to accuracy and objectivity in cost measurement, analysis of activities, selection of causes for accurate costs and measurement of outputs in the reports to make sound management decisions.